Liderazgos latinoamericanos: ALBA-TCP y Unasur como opciones de la integración regional. - Morales Fajardo, María Esther (CONfines de Relaciones Internacionales y Ciencia Política)
In this paper two schemes of integration are analyzed in Latin America: ALBA-TCP and Unasur, both as alternatwes proposed by Venezuela and Brazil concerning about Latin-American integration. The objective is to analyze if these schemes follow the foreign policy of those countries and if they are determinant for the leadership in the region.